Seeing Dynamic Data Visualizations in Action Gapminder Tools - Kovács Péter (Statistics for Empowerment and Social Engagement, 2022)
Citizens need sophisticated ways of thinking in order to understand complex, real social and economic phenomena and to interpret relationships among social and business data correctly. Huge amounts of data, data sources and visualization tools provide an opportunity to illustrate complex relations within real data. At the same time, the misuse of these tools can lead to misinterpretations and in turn perhaps to poor decision making. The Gapminder Foundation has developed several visualization tools (using bubble charts, trend lines, ranks, maps, etc.) in order to facilitate the exploration of complex relationships between variables, to rank countries, and to explore things such as time series, age distributions and income distributions. The goals of this chapter are to: show these different tools in action in classes exploring poverty and the ageing society; to describe their advantages and disadvantages; and to compare.